Arthroscopic reconstruction of anterior cruciate ligaments with allograft: single-tunnel single-bundle versus single-tunnel double-bundle techniques - Zhenhan Deng; Yizi Zheng; Zhiqin Deng; Changwei Lu; Yihua Wu; Kang Chen; Zicai Fu; Hui Zhang; Wei Lu; Weimin Zhu (Journal of Orthopaedics and Traumatology, 2022)
Abstract Purpose To compare the clinical results of anterior cruciate ligament (ACL) reconstruction using the single-tunnel single-bundle (STSB) technique versus the single-tunnel double-bundle (STDB) technique. Methods This was a retrospective, single-center, single-surgeon study based on data collected from March 2012 to June 2013. According to our inclusion/exclusion criteria, a total of 78 patients (64 males, 14 females; mean age, 25.1 years) who underwent arthroscopic ACL reconstruction with anterior tibialis tendon allografts through either the STSB technique (36 cases) or the STDB technique (42 cases) in our department were recruited. The International Knee Documentation Committee (IKDC), Lysholm, and Tegner scores were used to evaluate the subjective function of the knee joint during the postoperative follow-up. The Lachman test and pivot shift test were used to objectively assess the stability of the knee. Results The average follow-up duration was 24.9 ± 1.8 months in the STSB group and 24.6 ± 1.7 months in the STDB group (P > 0.05). Patients in both groups recovered to the preoperative sports level with few complications. The postoperative Lysholm score (86.1 ± 7.5 vs. 47.7 ± 9.0 in the STSB group; 87.0 ± 7.1 vs. 48.2 ± 8.3 in the STDB group), IKDC score (87.8 ± 7.2 vs. 49.3 ± 6.1 in the STSB group; 88.7 ± 6.6 vs. 49.8 ± 6.3 in the STDB group), Tegner score (6.5 ± 1.3 vs. 2.5 ± 1.3 in the STSB group; 6.6 ± 1.2 vs. 2.6 ± 1.2 in the STDB group), Lachman test positive rate (8.3% vs. 89.9% in the STSB group; 7.1% vs. 85.7% in the STDB group), and pivot shift test positive rate (27.8% vs. 63.9% in the STSB group; 7.1% vs. 69.0% in the STDB group) were significantly improved compared to the preoperative status in both groups (P < 0.05). However, no statistically significant difference was observed between the two groups at the final follow-up (P > 0.05), except for the pivot shift test positive rate in the STDB group versus the STSB group (7.1% vs. 27.8%, P < 0.05). Conclusions The STDB technique achieved a satisfactory clinical outcome with better rotational stability compared to the traditional STSB technique and therefore provided an effective option for ACL reconstruction. Level of evidence Case series, Level IV.